Halal Supply Chain Risk Analysis Using an Integrated FMEA–SCOR and Monte Carlo Simulation Approach to Assess Blockchain Technology Adoption Feasibility in Indonesian Halal Food MSMEs - Muhammad Budi Adiputra Reski; Nurul Chairany; Rabiatul Adawiyah (Journal of Industrial System Engineering and Management, 2026)
Indonesia's halal industry is one of the fastest-growing components of the national economy, with the food and beverage sub-sector posting 5.87% year-on-year growth in 2024 and total halal consumption reaching IDR 545.6 trillion in 2022, yet only 4.4% of the country's roughly 28 million Micro and Small Enterprises (MSEs) had been halal-certified by May 2024, making supply chain readiness a critical concern ahead of the mandatory halal certification deadline of October 2026. This study integrates Failure Mode and Effect Analysis (FMEA) with the Supply Chain Operations Reference (SCOR) model to identify and prioritize risk points along the MSME halal food supply chain, and then applies a 10,000-iteration Monte Carlo simulation to quantify the ex-ante reduction in aggregate Risk Priority Number (RPN) achievable through blockchain technology adoption. Twenty-eight risk points were mapped across the Plan, Source, Make, Deliver, and Return processes, with an aggregate Total RPN of 4,180 before mitigation; the five highest-RPN risks all relate to traceability gaps and halal-document integrity, with the Make stage contributing 39.2% of total risk. Simulation results show that blockchain adoption produces a non-linear, diminishing-returns reduction profile: 21.2% risk reduction at 25% penetration, 41.4% at 50%, 62.0% at 70%, and 79.3% at 90%. The optimal investment point is estimated at p ≈ 0.70, beyond which marginal benefits decline sharply. The findings provide a practical, quantitative framework for MSME operators, Badan Penyelenggara Jaminan Produk Halal (BPJPH), and Lembaga Pemeriksa Halal (LPH) to design phased blockchain adoption supported by ecosystem readiness in regulation, organization, and technology.